GEI reduction in the Dining Room of the National Mayor University of San Marcos - Vera Vásquez, Miguel Edgardo (2023)
The analysis of GHG emissions in the University Dining Room, through the application of Environmental Management is based on a quantitative approach, with a non-experimental design and of the applied type, a study that was carried out with the support of the dining room staff. Applying a survey and a questionnaire, a registration form and direct observation, collecting the information. This study made it possible to determine that the transport of personnel, waste, the consumption of: diesel, propane gas, electric energy are factors that generate GHG. The results show the conditions of GHG emissions in the dining room, recommending measures to control non-compliance with environmental quality standards. The statistics indicate that 84.6% of the personnel know the sources of GHG emissions; 84.6% know about waste treatment; 61.5% indicated the inappropriate use of gas. In the development of this research, the technical and regulatory requirements have been met, which is why its recommendations will be a contribution to university and environmental management. This study is a starting point to develop environmental awareness at UNMSM, a role that the Dean of America must fulfill as an environmentally responsible institution.